Advancing Conservation by Understanding and Influencing Human Behavior. Issue 2 (19th October 2016) - Reddy, Sheila M.W.; Montambault, Jensen; Masuda, Yuta J.; Keenan, Elizabeth; Butler, William; Fisher, Jonathan R.B.; Asah, Stanley T.; Gneezy, Ayelet
Abstract: Behavioral sciences can advance conservation by systematically identifying behavioral barriers to conservation and how to best overcome them. Behavioral sciences have informed policy in many other realms (e.g., health, savings), but they are a largely untapped resource for conservation. We propose a set of guiding questions for applying behavioral insights to conservation policy. These questions help define the conservation problem as a behavior change problem, understand behavioral mechanisms and identify appropriate approaches for behavior change (awareness, incentives, nudges), and evaluate and adapt approaches based on new behavioral insights. We provide a foundation for the questions by synthesizing a wide range of behavior change models and evidence related to littering, water and energy conservation, and land management. We also discuss the methodology and data needed to answer these questions. We illustrate how these questions have been answered in practice to inform efforts to promote conservation for climate risk reduction. Although more comprehensive research programs to answer these questions are needed, some insights are emerging. Integrating two or more behavior change approaches that target multiple, context‐dependent factors may be most successful; however, caution must be taken to avoid approaches that could undermine one another (e.g., economic incentives crowding out intrinsic incentives).